2019
DOI: 10.1155/2019/5897505
|View full text |Cite
|
Sign up to set email alerts
|

The Association between PON1 (Q192R and L55M) Gene Polymorphisms and Risk of Cancer: A Meta-Analysis Based on 43 Studies

Abstract: Q192R and L55M polymorphism were considered to be associated with the development of multiple cancers. Nevertheless, the results of these researches were inconclusive and controversial. Therefore, we conducted a meta-analysis of all eligible case-control studies to assess the association between PON1 (Q192R and L55M) gene polymorphisms and risk of cancer. With the STATA 14.0 software, we evaluated the strength of the association by using the odds ratios (ORs) and 95% confidence intervals (CIs). A total of 43 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Their results showed that PON1 rs854560 genetic polymorphisms may be associated with the risk of BC. However, they have Pan et al, (2019) in meta-analysis reported that the PON1 rs662 is associated with decrease of breast cancer risk. Their results showed an increased risk in the Caucasian and Asian population as well as HB group and PB group.…”
Section: Discussionmentioning
confidence: 97%
“…Their results showed that PON1 rs854560 genetic polymorphisms may be associated with the risk of BC. However, they have Pan et al, (2019) in meta-analysis reported that the PON1 rs662 is associated with decrease of breast cancer risk. Their results showed an increased risk in the Caucasian and Asian population as well as HB group and PB group.…”
Section: Discussionmentioning
confidence: 97%
“…In a meta-analysis based on 43 studies, PON1-L55M was found to be a risk factor in the genesis of breast cancer in the Caucasian and Asian population (OR = 2.19). Meanwhile, PON1-Q192R polymorphisms correlated with the decreased risk in breast cancer in the same population as above (OR = 0.64) [37].…”
Section: Paraoxonase 1 (Pon1)mentioning
confidence: 59%
“…Decreased serum activity of PON1 has been reported in some cancer patients [64]. The polymorphism of PON1 gene has been used as a prediction for cancer susceptibility due to its ability to detoxify the products of oxidative stress [65] and considered a risk factor for the occurrence of certain cancer types like breast, prostate and hematologic cancers [66]. In the present study, there was a significant reduction in the plasma activity of arylesterase in the leukemic rats which may be due to overwhelming pro-oxidant effect of benzene intoxication leading to oxidative stress condition.…”
Section: Discussionmentioning
confidence: 99%